(untitled) (Research, Society and Development, 2022)
Population aging promotes meaningful changes in social structures, increasing the presence of older people in the labor market. By exposing this context, this research aims to analyze the following questions: the representation of work for older people, aging at work, and the relationship between the continuity of elderlies in the labor world and the worker’s health. A semi-structured interview technique and a focus group with 16 elderly professionals were applied. Data were analyzed using a thematic content analysis technique. As analytical categories, it was highlighted the positive and negative aspects of the elderly at work, the representation of work for the elderly’s lives and factors that affect the worker’s health. The positive images of the elderly related to work were shown to be anchored to the experience and responsibility in face of work relationships. On the other hand, the negative view was mainly linked to the stigma of unproductivity. Working in old age was associated with income supplementation and personal development. The health of elderly people in work environments was mentioned as being affected by working organizations, including unfitted furniture and working hours, the lack of knowledge of new technologies, intergenerational conflicts and age discrimination. Therefore, it is demanded the development of public policies in order to reduce risk factors for working elderlies health.